Present Status of Ganges River Dolphins Platanista gangetica gangetica (Roxburgh, 1801) in the Turag River, Dhaka, Bangladesh - Baki, Mohammad Abdul; Bhouiyan, Naser Ahmed; Islam, Md. Saiful; Alam, Shayer Mahmood Ibney; Shil, Shibananda; Hossain, Md. Muzammel (International Journal of Zoology, 2017)
Freshwater ecosystem degradation in the Turag River basin is increasing due to rising human settlement, reduced water flow during the dry season, new large land development projects, and toxic emissions caused by brick kilns. The population of river dolphins was estimated through surveys carried out from December 2012 to November 2013. Surveys were conducted on a fortnightly basis. The dolphins were counted within an 18.4 km stretch (known to be the most polluted stretch) of the 75 km long river. A total of 62 dolphin sightings were recorded, both as individual sightings and as groups. The highest monthly count was in August. The best-high-low estimates of 9-11-7 individuals were recorded in August 2013 in river ecology. Seasonal changes in spatial distribution were observed. The survey revealed that rising floodwater stimulated an increase in the dolphin population in the study area from July to October. The maximum encounter rate was also 0.49 sightings km−1 for the month of August. The sightings and encounter rates of dolphins were lower from December to July (dry and premonsoon period) likely due to reduced water flow and adverse water quality of this river.